Health Promotion Interventions for Tackling Type 2 Diabetes in Surabaya: A Multi-Perspective Root Cause Analysis - Zhalmagambetov, Bakhytbek; Hendrati, Lucia Yovita; Dwi Yuliandari, Rosita (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2026)
Background: Type 2 Diabetes Mellitus (T2DM) is a metabolic disorder. In Surabaya, it has been a growing public health challenge, with rising prevalence and increasing strain on people and healthcare. Objective: The purpose was to identify a root cause of T2DM, and to provide possible solutions to tackle the problem. Methods: A mixed-method design was used. Qualitative data were obtained from three structured interviews capturing the perspectives of a patient, a physician, and a community health center worker. Problems contributing to DMT2 were brainstormed and then prioritized using the USG method. A “web of causation” approach was applied to identify the root cause of the problem. Results: Unhealthy lifestyle behaviors were prioritized based on the USG analysis. Knowledge insufficiency was identified as the root cause. Two evidence-based solutions are proposed: (1) mobile messaging and (2) “point-of-decision” education in workplaces, canteens, and other public spaces. Conclusion: WhatsApp/SMS education through Puskesmas registries and “point-of-decision” education in public spaces are feasible interventions to enhance diabetes knowledge, promote healthier eating, and reduce sugary product consumption.